ДОПРОС В СУДЕБНОМ ЗАСЕДАНИИ ЕГО ПОНЯТИЕ, ЗНАЧЕНЕЕ И ОСОБЕННОСТИ – КАК ФАКТОР, ФОРМИРУЮЩИЙ И ОБУСЛОВЛИВАЮЩИЙ ТАКТИКУ ПРОКУРОРА ПРИ ПОДДЕРЖАНИИ ГОСУДАРСТВЕННОГО ОБВИНЕНИЯ (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the problem of interrogation during the court session and the importance of formation the tactics of public prosecutor in thisprocess and detailed analysis of its peculiarities. To determine the matter of interrogation the author used the judicial statistics, archives, questionnaire and thecarried out analysis is summed up.